Reelin controls neuronal positioning by promoting cell-matrix adhesion via inside-out activation of integrin α5β1 - Sekine, Katsutoshi; Kawauchi, Takeshi; Kubo, Ken-Ichiro; Honda, Takao; Herz, Joachim; Hattori, Mitsuharu; Kinashi, Tatsuo; Nakajima, Kazunori (Neuron (Cambridge, Mass.), 2012)
Birthdate-dependent neuronal layering is fundamental to neocortical functions. The extracellular protein Reelin is essential for the establishment of the eventual neuronal alignments. Although this Reelin-dependent neuronal layering is mainly established by the final neuronal migration step called "terminal translocation" beneath the marginal zone (MZ), the molecular mechanism underlying the control by Reelin of terminal translocation and layer formation is largely unknown. Here, we show that after Reelin binds to its receptors, it activates integrin α5β1 through the intracellular Dab1-Crk/CrkL-C3G-Rap1 pathway. This intracellular pathway is required for terminal translocation and the activation of Reelin signaling promotes neuronal adhesion to fibronectin through integrin α5β1. Since fibronectin is localized in the MZ, the activated integrin α5β1 then controls terminal translocation, which mediates proper neuronal alignments in the mature cortex. These data indicate that Reelin-dependent activation of neuronal adhesion to the extracellular matrix is crucial for the eventual birth-date-dependent layering of the neocortex.